Seasonal variation in meat quality of Angus steers raised in a Mediterranean forage-fed system: A farm case study - Viviana Bolletta; Valentina Roscini; Emanuele Lilli; Chiara Fodaroni; Jacopo Gabriele Orlando; Valentino Mercati; Bernardo Valenti; Mariano Pauselli (PLoS ONE, 2026)
This study monitored the impact of seasonal feeding variability on meat quality traits in forage-fed Angus steers. A total of 38 steers were selected based on their diets during the last three months before slaughter: a hay-based winter diet (WIN), a spring fresh-forage-based diet (SPR), or a summer fresh-forage-based diet (SMM). Meat quality was assessed through fatty acid profiling, antioxidant capacity, myoglobin content, color stability, and lipid oxidation during refrigerated storage. Principal components and linear discriminant analysis were used to uncover, underlying patterns, and classify the observations based on the multivariate profile. Meat fatty acids showed limited variation across seasons, with differences restricted to minor polyunsaturated fatty acids. The n-6/n-3 ratio and other health-related lipid indices remained within recommended values despite the feeding season. Meat from SPR and SMM animals showed higher α - and γ -tocopherol levels and greater myoglobin content compared to WIN meat. Color parameters and lipid oxidation were moderately affected by diet and storage time, with better stability observed in meat from animals receiving fresh forage. Despite the subtle impact on individual quality traits, multivariate discriminant analysis effectively differentiated meat samples based on the feeding season, achieving 89.5% correct classification. The most discriminating variables included fatty acids (17:1 c 9 , 18:1 t 10, 22:0, 22:5 n-6), color attributes (b*), and oxidative markers (TBARS, metmyoglobin %). With the caution due to the nature of the study, these findings suggest that while single quality indicators may not strongly reflect dietary differences, their combination may provide a tool to trace seasonal feeding strategies in grass-fed beef production.